Hirudin C-Terminal Fragments lnhibit Thrombin Induced Neutrophil Chemotaxis - Rowand, Judith K; Marucha, Philip; Berliner, Lawrence J (Thrombosis and Haemostasis, 1992)
Since native hirudin blocks the thrombin induced chemotaxis response of neutrophils, we examined whether hirudin C-terminal peptides were also capable of this inhibition. The studies showed that thrombin induced human neutrophil chemotaxis was effectively blocked by the C-terminal hirudin peptide analogs, Gly-Asp-Phe-Glu-Glu-Ile-Pro-Glu-Glu-Tyr-Leu-Gin (12-mer[54-65]) and Thr-Pro-Lys-Pro-Gln-Ser-His-Asn-Asp-Gly-Asp-Phe-Glu-Glu-Ile-Pro-Glu-Glu-Tyr-Leu-Gln (21-mer[45-65]). Furthermore, neither peptide had an effect on formyl-L-methionyl-L-leucyl-L-phenylalanine induced chemotaxis. The results suggest that binding of the hirudin C-terminal peptides block the thrombin chemotactic domain.